2018
DOI: 10.3389/fpsyg.2018.01741
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity and Invariance of the 7-Item Generalized Anxiety Disorder Scale (GAD-7) Among Populations With and Without Self-Reported Psychiatric Diagnostic Status

Abstract: The 7-item Generalized Anxiety Disorder Scale (GAD-7) is commonly used to monitor anxiety symptoms. However, its factor structure has been inconsistent among competing models: unidimensional, two-dimensional, or higher order models. Additionally, it is unknown whether the scale has measurement invariance between populations with and without self-reported psychiatric diagnostic status. Participants were Japanese adults with self-reported anxiety disorder (AD; n = 479), self-reported AD and major depressive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 30 publications
7
52
1
1
Order By: Relevance
“…Similar findings also were reported for primary care patients (Jordan et al, 2017;Johnson et al, 2019), psychiatric patients (Dear et al, 2011;Kertz et al, 2013;Konkan et al, 2013;Rutter and Brown, 2017;Johnson et al, 2019), infertility patients (Omani-Samani et al, 2018), the general population in several countries (Konkan et al, 2013;Sousa et al, 2015;Hinz et al, 2017), adolescents (Tiirikainen et al, 2019), individuals receiving care in a traditional medicine department in China (Zeng et al, 2013), and in non-English speakers (Mills et al, 2014;Sousa et al, 2015;Ahmad et al, 2017). Further, the goodness-of-fit findings parallel those reported for populations with varying characteristics (García-Campayo et al, 2012;Mills et al, 2014;Bartolo et al, 2017;Hinz et al, 2017;Rutter and Brown, 2017;Doi et al, 2018;Lee and Kim, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Similar findings also were reported for primary care patients (Jordan et al, 2017;Johnson et al, 2019), psychiatric patients (Dear et al, 2011;Kertz et al, 2013;Konkan et al, 2013;Rutter and Brown, 2017;Johnson et al, 2019), infertility patients (Omani-Samani et al, 2018), the general population in several countries (Konkan et al, 2013;Sousa et al, 2015;Hinz et al, 2017), adolescents (Tiirikainen et al, 2019), individuals receiving care in a traditional medicine department in China (Zeng et al, 2013), and in non-English speakers (Mills et al, 2014;Sousa et al, 2015;Ahmad et al, 2017). Further, the goodness-of-fit findings parallel those reported for populations with varying characteristics (García-Campayo et al, 2012;Mills et al, 2014;Bartolo et al, 2017;Hinz et al, 2017;Rutter and Brown, 2017;Doi et al, 2018;Lee and Kim, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…If we do not evaluate measurement invariance, the comparison of means between male and female medical stuffs could be problematic. A number of studies (Wu and Huang, 2014;Doi et al, 2018) have demonstrated that other depression and anxiety measurement scales have reliable measurement invariance (e.g., Beck Depression Inventory-II, the 7-item Generalized Anxiety Disorder Scale). Some studies have examined the measurement invariance of the DASS-21 across genders (Gomez et al, 2014;Jafari et al, 2017;Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The GAD-7 was translated into Japanese through back translation 28 with prior studies confirming the reliability and validity of the Japanese version. 28,29,30 The sensitivity and specificity of the Japanese version of the GAD-7 were 88% and 82%, respectively. 28 For each item, responses are rated on a 4-point scale from 0 to 3, with higher scores representing increased levels of anxiety (total score range 0-21).…”
Section: Measures Of Mental Health Statusmentioning
confidence: 97%